(untitled) (Razi Medical Journal, 2025)
Nurses make up by far the largest group of healthcare workers in any part of the world and have an important role to play in the direct management of human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) patients, and consequently face a high risk of infection. This study aimed to assess the awareness about HIV and AIDS among nurses in Misurata, Libya. The study was conducted among 351 nurses working in public hospitals in the province of Misurata, Libya. A validated self-administered questionnaire was used to investigate the nurses’ awareness of HIV and AIDS. Out of the participants, 96 (27.4 %) were male and 255 (72.6 %) were female. Most of the participants were above the 20 years age of. The results revealed that the overall level of awareness about HIV/AIDS transmission was low, as only 133 (38%) of the nurses had a good level. The level of awareness was significantly affected by the demographics and work experience of the respondents. Most of the nurses who participated in this study lacked knowledge of HIV. Active educational interventions, such as regular HIV awareness programmes in hospitals, are required to improve knowledge about AIDS. Also, the nursing programme curriculum should be revised and updated in Libya to better prepare nurses to deal with incidences of HIV/AIDS.